PERTUMBUHAN EKONOMI DAN PENDAPATAN KABUPATEN BOJONEGORO SEBELUM DAN SESUDAH PEMEKARAN WILAYAH - UMMI SHOLIHAH, SITI Ummi (Jurnal Akuntansi AKUNESA, 2014)
Abstract: Bojonegoro become a city known for the presence of oil mining in the district. Bojonegoro District is fairly extensive district with 27 sub-districts including new sub-districts formed the District Gayam. Of the expansion of the mining area and the existing oil is expected to occur both in terms of the development of economic, social and political. From an economic point of the economic situation of a region can be seen from the Gross Domestic Product (GDP) District. Of these two phenomena, namely expansion area and the presence of the oil to see how economic growth and revenue Bojonegoro. This study used a qualitative research by analyzing and describing the data obtained in the form of GDP Bojonegoro, Bojonegoro total revenue by observing certain sources of revenue and revenue from the district and sub-district related to the state of the economy before and after the expansion area. From the research that has been done, the regional growth is not significant effect on economic growth is evident from the amount of GDP and total revenue Bojonegoro. Redistricting only adds to the doorway money for Kabupten Bojonegoro. Keywords : Expansion of the region , Gross Domestic Product , Local Revenue